It is hard to beat the monkeys: On the value of asymmetric fundamental information in asset markets - Michael Kirchler (University of Innsbruck, Department of Public Finance, 2008)
In this paper we present results from experimental asset markets and simulations with traders who receive asymmetric information about the fundamental value of an asset. In the experimental markets with repetition insiders outperform the market and uninformed computerized random traders (monkeys) perform equally well compared to average informed traders. This is in line with the results of the equilibrium simulation output in which traders choose between a random strategy and their fundamental strategy. We further find that pattern of average informed not being able to beat the uninformed is not due to their overconfidence but due to the asymmetric information structure of the market.
Keywords: C91; C92; G14; 330; information economics; experimental economics; agent-based model; overconfidence; value of information